Influence of retarder admixtures on the hydration, rheology, and compressive strength of white Portland cements under different temperatures - Rayara Costa; Thiago Cardoso; Maxwell Degen; Laura Silvestro; Erich Rodríguez; Ana Paula Kirchheim (Cement, 2023)
White cement is characterized by higher tricalcium aluminate (C3A) contents than conventional Portland cement; thus, it can present a reduced setting time, especially under hot weather conditions, limiting the material's application period. An approach to delay these materials' setting time is using retarder admixtures (RA). Nevertheless, there is a knowledge gap regarding the effect of RA on the rheological properties of white cement. This study aimed to evaluate the effect of two types of RA on the mini-slump, rheological parameters, hydration kinetics, and compressive strength of two white cements. Furthermore, the effect of temperatures of 25 and 40 ⁰C on the performance of the admixtures was also assessed. Both RA showed a dispersing effect, reducing cement pastes' dynamic yield stress and plastic viscosity. Moreover, the admixtures extended the induction period of cement hydration by up to 15.4 h without significantly affecting the 72-h cumulative heat at a temperature of 25 ⁰C. At 40 ⁰C, both RA exhibited a lower dispersing and retarding effect. Although RA delayed the initial hydration reactions of the WC, it enhanced the mechanical performance of the mortars after three days of hydration.